Functional Components and Roles of the University Teacher in Distance Education - Glukhov, Gennady Vasilyevich; Gromova, Tatiana Vladimirovna (International Review of Management and Marketing, 2016)
The aim of the article is to define the roles and functions of a university teacher in the distance learning system essential both for massive online education and blending training. The changes in the activity of university teachers are necessary if they want to remain competent and meet the new requirements of work in the environment of information and communication technologies. The article identifies specific features of the university teacher's activity in the distance learning system compared with the so called “traditional teacher” and presents the authors' dynamics of gradual complication of the role of the distance learning teacher starting with the simplest one - operator of didactic tools to sophisticated ones, such as the expert, the author of the course. In the course of research the functional-role model of activities of distance learning university teacher was developed and these functions and roles were described. Development of the functional-role model reveals the essence of the main functional components of pedagogical activity of the distance learning university teacher such as project of the learning process, support and development of students, managerial, control and diagnostic, information and informative, motivational, organizational-activity, consulting, communicative and reflexive functions. Keywords: Distance education, Distance learning, Distance learning teacher, Functional-role model, Information and communication technologies, online educational learning environments JEL Classification: A19